Metformin Improves the Prognosis of Adult Mice with Sepsis-Associated Encephalopathy Better than That of Aged Mice. (4th May 2022) - Song, Gaofei; Liang, Huoyan; Song, Heng; Ding, Xianfei; Wang, Dong; Zhang, Xiaojuan; Sun, Tongwen
Abstract : Sepsis-associated encephalopathy (SAE) is often associated with increased ICU occupancy and hospital mortality and poor long-term outcomes, with currently no specific treatment. Pathophysiological mechanisms of SAE are complex and may involve activation of microglia, multiple intracranial inflammatory factors, and inflammatory pathways. We hypothesized that metformin may have an effect on microglia, which affects the prognosis of SAE. In this study, metformin treatment of mice with SAE induced by lipopolysaccharide (LPS) reduced the expression of microglia protein and related inflammatory factors. Poor prognosis of SAE is related to increased expression of tumor necrosis factor- α (TNF- α ) and interleukin-1 beta (IL-1 β ) in brain tissues. Levels of inflammatory cytokines produced by LPS-induced SAE mouse microglia were significantly increased compared with those in the sham group. In addition, ionized calcium-binding adapter molecule 1 (Iba-1) was significantly reduced in metformin-treated SAE mice compared with untreated SAE mice, suggesting that metformin can reduce microgliosis and inhibit central nervous system inflammation, thereby improving patient outcomes. In conclusion, our results stipulate that metformin inhibits inflammation through the adenosine 5 ′ -monophosphate (AMP-) activated protein kinase pathway by inhibiting nuclear factor kappa beta (NF- κ B). Metformin can partially reverse the severe prognosis caused by sepsis by blocking microglial proliferation and inhibiting the production of inflammatory factors.